Farmers perception and criteria for cassava variety preference in Cameroon - Njukwe, E.; Hanna, R.; Kirscht, H.; Araki, S. (Kyoto University, 2013)
To assess farmers’ perception and criteria for cassava variety preference prior to the dissemination of improved varieties in Cameroon, field visits were organized at the Mbalmayo research farm of International Institute of Tropical Agriculture (IITA ) during the vegetative and harvest periods, and a sensory quality test was conducted in a participatory manner. Parameters recorded were statistically analyzed using analysis of variance procedure (ANO - VA ), resulting in the selection of five varieties for multilocational testing and demonstration. To complement this effort, thirty cassava farmers in Ebolowa, Bertoua, Bamenda, Ngaoundere making a total of one hundred and twenty were interviewed following structured questionnaires, and their fields assessed. Results show that farmers cultivate many varieties of cassava for different uses but prefer early maturing variety (96.7%), high yield (89.2%), and resistant to pests and diseases (88.3%). In addition, there was regional preference. Farmers in Ebolowa and Bertoua preferred leafy, sweet roots and early branching varieties (TMS -92/0326, TMS - 96/0023) while those in Bamenda and Ngaoundere preferred tall, drought tolerant (TMS - 92/0057), fibrous (TMS -96/1414) for gari (roasted cassava granules) and in some cases flowering varieties (M94/0121) for apiculture. Results served as feedback information to research, extension, policy makers and other stakeholders. This constitutes an attractive scheme for deployment of the improved varieties and complements programs of the Cameroonian government for roots and tuber (PNDRT ), with the main objective to increase the productivity of cassava.